Metabolic remodeling maintains a reducing environment for rapid activation of the yeast DNA replication checkpoint. (14th January 2022) - Li, Lili; Wang, Jie; Yang, Zijia; Zhao, Yiling; Jiang, Hui; Jiang, Luguang; Hou, Wenya; Ye, Risheng; He, Qun; Kupiec, Martin; Luke, Brian; Cao, Qinhong; et al.
Abstract: Nucleotide metabolism fuels normal DNA replication and is also primarily targeted by the DNA replication checkpoint when replication stalls. To reveal a comprehensive interconnection between genome maintenance and metabolism, we analyzed the metabolomic changes upon replication stress in the budding yeast S. cerevisiae . We found that upon treatment of cells with hydroxyurea, glucose is rapidly diverted to the oxidative pentose phosphate pathway (PPP). This effect is mediated by the AMP‐dependent kinase, SNF1, which phosphorylates the transcription factor Mig1, thereby relieving repression of the gene encoding the rate‐limiting enzyme of the PPP. Surprisingly, NADPH produced by the PPP is required for efficient recruitment of replication protein A (RPA) to single‐stranded DNA, providing the signal for the activation of the Mec1/ATR–Rad53/CHK1 checkpoint signaling kinase cascade. Thus, SNF1, best known as a central energy controller, determines a fast mode of replication checkpoint activation through a redox mechanism. These findings establish that SNF1 provides a hub with direct links to cellular metabolism, redox, and surveillance of DNA replication in eukaryotes. Synopsis: While nucleotide metabolism is known to be tightly linked to DNA replication and repair, this work addresses more general yeast metabolome remodeling in response to replication stress, revealing a role for SNF1/AMPK in maintenance of a reductive cellular milieu that facilitates ssDNA binding by RPA. Hydroxyurea treatment diverts glucose into the oxidative pentose phosphate pathway. Sugar metabolism rewiring in response to replication stress is mediated by AMP‐dependent kinase SNF1. SNF1 phosphorylates transcription factor Mig1 to derepress ZWF1/G6PD transcription. Cellular redox state regulates RPA loading and S‐phase checkpoint activation. Abstract : Genotoxic effects may underlie the long‐lasting proliferative arrest triggered by anti‐cancer drugs that cause G1 phase pausing.